A Fair Go for All: A Problematic Contribution to Anti-racism Praxis in Aotearoa - Came, H (Auckland University of Technology, 2013)
In New Zealand, the Human Rights Commission is the lead agency in countering institutional racism. They have recently undertaken a major research project, A Fair Go For All (Human Rights Commission 2011), to inform the development of a national strategy/approach to counter structural discrimination. This paper, from an activist scholarship standpoint argues their chosen approach has ignoring the power relations inherent in researching racism. Furthermore their approach has minimised both the historic element of racism against Māori and the significance of Te Tiriti o Waitangi to anti-racism praxis in Aotearoa. Rather than endorse an ad hoc approach with a focus on practitioner bias (personally-mediated racism), and addressing ethnic inequalities (the outcome of institutional racism) this paper advocates for a Tiriti based systems change approach to transform institutional racism as it manifests in the neo-colonial context of Aotearoa.
Keywords: Institutional racism; anti-racism praxis; Activist scholarship; Te Tiriti o Waitangi